2008
DOI: 10.1021/ma702445e
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement Relaxation Time in Polyethylene: Simulation versus Experimental Data

Abstract: A combined computer simulation and experimental study describing the viscoelastic properties of linear polyethylene is presented. For the simulation, a set of C1000 polyethylene models were equilibrated using advanced Monte Carlo moves. Then, MD trajectories were calculated. From these simulations the entanglement molecular weight, M e, and the entanglement relaxation time, τe, were directly obtained. By introducing the experimental value for the plateau modulus and the simulated values for M e and τe into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
53
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 36 publications
12
53
1
Order By: Relevance
“…MSL 50 CH 2 (BC: 20/1000 C) was the critical length to form lamellae crystal in precisely branched polyethylene crystallization. This critical MSL was confirmed that 1 or 2 full folds and 3 edge folds formed in the linear PE chain simulation of 192 CH 2 . When BC above 30/1000 C, there was no folds at all for one MSL, neither full nor edge fold.…”
Section: Resultssupporting
confidence: 72%
“…MSL 50 CH 2 (BC: 20/1000 C) was the critical length to form lamellae crystal in precisely branched polyethylene crystallization. This critical MSL was confirmed that 1 or 2 full folds and 3 edge folds formed in the linear PE chain simulation of 192 CH 2 . When BC above 30/1000 C, there was no folds at all for one MSL, neither full nor edge fold.…”
Section: Resultssupporting
confidence: 72%
“…This is discussed later. Other methods of determining entanglements include: characterization by neutron spin‐echo, NMR relaxation methods, and Monte Carlo simulations . However, these methods are still not an alternative to the rheological research.…”
Section: Characterization Of Entanglementsmentioning
confidence: 99%
“…Thus, without the enhancement of α, the above multiscale computational framework cannot capture the correct relaxation behavior of these polydisperse chains. Since the PDI values of HPB TM polymersare rather small ( 1.1) [334], while they are as large as 1.8 to 2.9 for PEs [335], a large α = 0.7 value has been chosen for HPBs and a small one, α = 0.3, for PEs when t > τ d . With the enhancement of α, the predicted G(t) is in agreement with experimental results, which further confirms the fractional diffusive behavior of polydisperse chains.…”
Section: (A) (B)mentioning
confidence: 99%